(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The arduous life path and work of poetess Rana Uzokova from Surkhan, Sharof Rashidov "Article of Rana, people who have studied the life and work of the poetess, Akkurgan village, Zharkurgan district, Samarkand literary environment, the years of the Second World War.